Profile of Dyspepsia Patients in Mangusada Hospital - Dewa Ayu Erica Fleury; Putu Indah Budi Apsari; Sri Masyeni (Universitas Malahayati, 2026)
ABSTRACT Dyspepsia is a common upper gastrointestinal disorder that may reduce patients’ quality of life. The high number of dyspepsia visits at Mangusada Regional General Hospital, Badung, throughout 2024 highlights the need to understand patient characteristics as a basis for clinical evaluation and decision-making. This study aimed to describe the characteristics of patients with dyspepsia based on age, sex, clinical symptoms, comorbidities, medication use, andendoscopic examinations at Mangusada Regional General Hospital in 2024. This study employed a descriptive observational design with a cross-sectional approach. Data were obtained from the medical records of dyspepsia patients attending the Internal Medicine outpatient clinic during 2024. Samples were selected using simple random sampling, and the data were analyzed descriptively. The results showed that dyspepsia patients were generally olderadults and more frequently female. Common clinical symptoms included epigastric pain, nausea, and bloating, withsome patients experiencing multiple complaints. A proportion of patients had comorbid conditions, most commonly hypertension and diabetes mellitus. Dyspepsia management in this study was predominantly empirical, with acid-suppressive therapy, particularly Proton Pump Inhibitors (PPIs), being the most commonly used treatment. Endoscopic examinations were performed selectively based on clinical indications. In conclusion, dyspepsia patients at Mangusada Regional General Hospital in 2024 were mainly older adults presenting with upper gastrointestinal symptoms and were primarily managed using an empirical approach. These findings emphasize the importance of comprehensive clinical assessment and the selective use of therapeutic and diagnostic interventions in the management of dyspepsia. Keywords: Dyspepsia, Endoscopy, Medication Use, Patient Characteristics.